BENTUK EMOSI DAN PENANGANANNYA PADA ANAK AUTISM SPECTRUM DISORDER (ASD) USIA 15 TAHUN DI UPT REHABILTAS SOSIAL BINA GRAHITA TUBAN - Ni'mah, Malikhatun; Christiana, Elisabeth (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the emotional forms of autistic children and their handling by caregivers at the Bina Grahita Tuban Social Rehabilitation Unit. The study used a qualitative approach with a phenomenological method to understand the emotional experiences of autistic children in everyday life. The subject of the study was a 15-year-old autistic child living at the Bina Grahita Tuban Social Rehabilitation Unit, while the informants consisted of three caregivers directly involved in the mentoring process. Data were collected through observation and in-depth interviews, then analyzed through data reduction, data presentation, and drawing conclusions. Data validity was tested using technical triangulation. The results showed that autistic children displayed emotions of anger, anxiety, and joy in various situations. These emotions were triggered by changes in routine, differences in food portions, the removal of favorite items, and crowded environmental conditions. Children expressed emotions primarily through nonverbal behavior and responses due to limited verbal communication. Emotional management was carried out individually and situationally through reducing environmental stimuli, calm and patient mentoring, and temporary placement in a quieter room with supervision. This study concludes that handling the emotions of autistic children requires an understanding of the child's characteristics, patience, and consistent and continuous support.